2017
DOI: 10.1097/md.0000000000008161
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liraglutide versus sitagliptin both in combination with metformin in patients with type 2 diabetes

Abstract: Background:The aim of this systematic review was to evaluate the efficacy and safety of liraglutide versus sitagliptin both in combination with metformin in patients with type 2 diabetes and provide reference basis for rational use of clinical drugs.Methods:Several databases were searched, including Web of science, PubMed, Cochrane library, CNKI, and Wanfang database. Only randomized controlled trials (RCTs) of liraglutide versus sitagliptin both in combination with metformin up to 31 August 2016 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Liraglutide demonstrated superior glycemic control, greater weight loss, and better treatment satisfaction after 52 weeks as an add-on to metformin compared with another incretin-based therapy, sitagliptin [a dipeptidyl peptidase-4 (DPP-4) inhibitor] [ 9 ]. The findings were consistent with those observed at a shorter follow-up period [ 10 12 ], while gastrointestinal problems were common adverse reactions to liraglutide [ 13 ]. Based on data from the clinical trials, the annual mean cost per patient was estimated to be $5103–$6523 (2012 USD) lower with liraglutide than with sitagliptin to reach glycated hemoglobin (HbA1c) < 7.0% with no hypoglycemia or weight gain, and liraglutide was shown to be more cost-effective than sitagliptin after 5 years of use [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 88%
“…Liraglutide demonstrated superior glycemic control, greater weight loss, and better treatment satisfaction after 52 weeks as an add-on to metformin compared with another incretin-based therapy, sitagliptin [a dipeptidyl peptidase-4 (DPP-4) inhibitor] [ 9 ]. The findings were consistent with those observed at a shorter follow-up period [ 10 12 ], while gastrointestinal problems were common adverse reactions to liraglutide [ 13 ]. Based on data from the clinical trials, the annual mean cost per patient was estimated to be $5103–$6523 (2012 USD) lower with liraglutide than with sitagliptin to reach glycated hemoglobin (HbA1c) < 7.0% with no hypoglycemia or weight gain, and liraglutide was shown to be more cost-effective than sitagliptin after 5 years of use [ 14 , 15 ].…”
Section: Introductionsupporting
confidence: 88%
“…This finding suggests that in mice, GLP1 secretion is not the predominant mechanism for the glucose lowering effect of metformin. Of note, incretin-based therapies are approved for use as add-ons to the first line metformin monotherapy to further amplify clinical outcomes, which supports the contribution of GLP1-independent mechanisms to the glucose-lowering impact of metformin 164 .…”
Section: Effects Of Metformin On Glp1 Releasementioning
confidence: 88%
“…A recent real-world study has also highlighted the longterm effectiveness of liraglutide in this population [12]. A meta-analysis also demonstrated the efficacy and safety of liraglutide compared with sitagliptin when combined with metformin [23]. Furthermore, various studies sourcing data from clinical trials and claims data demonstrated better cost-effectiveness of liraglutide compared with sitagliptin, with any increases in pharmacy costs associated with liraglutide being offset by decreases in other diabetes-related medical expenses [13][14][15][16].…”
Section: Discussionmentioning
confidence: 98%